Choice experiments to elicit the users preferences for coastal erosion management : the case of Praia da Amorosa - Oliveira, Susana (2022)
Coastal erosion is a complex and increasingly important problem, largely due to its efects and management strategies. The current context of climate change, together with centuries of human occupation of shorelines, adds pressure for the development of sustainable coastal management policies, the success of which crucially depends on the consideration of all stakeholders? perspectives. This research investigates users? preferences over alternative options of coastal erosion management. Through the implementation of a discrete choice experiment, respondents? preferences regarding management alternatives are elicited, and their willingness to pay for alternatives? attributes is estimated. The results show that respondents prefer some interventions to mitigate the problem rather than no action, and prefer lighter intervention (palisades, gangways) to heavy infrastructures (rockflls, seawalls, groynes). Moreover, the results show the presence of preference heterogeneity and thus the need to use more fexible and complex models. Based on the results obtained, it is possible to drive some policy implications. First, the do-nothing option is not viable from the population?s standpoint; second, although some type of coastal erosion protection is demanded by the general population, the preferred approach is for light forms, contrary to the policy adopted in the last century, and still overwhelmingly present in the territory. Lastly, given the considerable heterogeneity in respondents? preferences, careful consideration of the welfare impact of coastal interventions by population segments is required.